2007
DOI: 10.1038/nrm2126
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of nuclear protein phosphatases

Abstract: The phosphorylation state of any protein represents a balance of the actions of specific protein kinases and protein phosphatases. Many protein phosphatases are highly enriched in, or exclusive to, the nuclear compartment, where they dephosphorylate key substrates to regulate various nuclear processes. In this review we will discuss recent findings that define the role of nuclear protein phosphatases in controlling transforming growth factor-beta (TGFbeta) and bone-morphogenetic protein (BMP) signalling, the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
329
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(339 citation statements)
references
References 113 publications
5
329
0
5
Order By: Relevance
“…Reversible protein phosphorylation by kinases and phosphatases is one of the most common mechanisms in controlling most, if not all, cellular processes [1]. Dephosphorylation of serine/threonine residues is regulated by two distinct groups of functionally diverse serine/threonine protein phosphatases, the PPM family (which includes PP2C) and the PPP family, which includes the type 1 (PP1) and the type 2A (PP2A, PP2B, PP3, PP4, PP5, PP6, and PP7) protein phosphatases.…”
Section: Dear Editormentioning
confidence: 99%
“…Reversible protein phosphorylation by kinases and phosphatases is one of the most common mechanisms in controlling most, if not all, cellular processes [1]. Dephosphorylation of serine/threonine residues is regulated by two distinct groups of functionally diverse serine/threonine protein phosphatases, the PPM family (which includes PP2C) and the PPP family, which includes the type 1 (PP1) and the type 2A (PP2A, PP2B, PP3, PP4, PP5, PP6, and PP7) protein phosphatases.…”
Section: Dear Editormentioning
confidence: 99%
“…Inhibitors of a PPM family phosphatase can activate 39 cleavage Most S/T phosphatases can be classified by catalytic subunit sequence homology into three superfamilies (Moorhead et al 2007): the phosphoprotein phosphatase (PPP) family, which includes PP1, PP2A, PP2B, PP4, PP5, and PP7; the protein phosphatase with Mg 2+ / Mn 2+ dependence (PPM), solely represented by the PP2Cs; and the DXDXT/V motif phosphatases, such as FCP1, which are specific for the C-terminal domain (CTD) of RNA Pol II. Although the CTD stimulates 39 cleavage in vitro (Hirose and Manley 1998), it does so independent of its CTD phosphorylation state (Hirose and Manley 1998;Ryan et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…As a class, they are expected to have similar structures and active sites (Stern et al 2007) and would therefore be expected to share sensitivity to the same inhibitors. While several of these paralogs are known to localize to the nucleus (Moorhead et al 2007), one in particular, PP2Cg (PPM1G), has been found to play a role in pre-mRNA splicing (Murray et al 1999;Allemand et al 2007), which is in turn coordinated with 39 cleavage (Niwa et al 1990;Kyburz et al 2006;Millevoi et al 2006). We detected PP2Cg at varying levels by Western blotting in our partially purified cleavage factors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Functional PP1 holoenzymes consist of a highly conserved ~35 kDa catalytic subunit (C) associated with a regulatory (R) subunit that is responsible for subcellular localisation and determines substrate specificity. While there are only a few genes (PP1cα, PP1cβ/δ, and PP1cγ) that code for catalytic subunit proteins, more than a hundred putative R subunits have been identified [35]. The naturally occurring toxins okadaic acid (OKA) and microcystin are potent inhibitors of the catalytic subunit of both PP1 and PP2A [36,37] and are thus widely used to study the role of these phosphatases in various contexts.…”
Section: Protein Phosphatase 1 (Pp1)mentioning
confidence: 99%